Hybrid Wind and Solar Photovoltaic Generation with Energy Storage Systems: A Systematic Literature Review and Contributions to Technical and Economic Regulations - Gabriel Nasser Doyle de Doile; Paulo Rotella Junior; Luiz Célio Souza Rocha; Ivan Bolis; Karel Janda; Luiz Moreira Coelho Junior (Energies, 2021)
The operation of electrical systems is becoming more difficult due to the intermittent and seasonal characteristics of wind and solar energy. Such operational challenges can be minimized by the incorporation of energy storage systems, which play an important role in improving the stability and reliability of the grid. The economic viability of hybrid power plants with energy storage systems can be improved if regulations enable the remuneration of the various ancillary services that they can provide. Thus, the aim of this study is to provide a literature review regarding the economic feasibility of hybrid wind and solar photovoltaic generation with energy storage systems and its legal and regulatory aspects. Observing the global tendency, new studies should address the technical and economic feasibility of hybrid wind and solar photovoltaic generation in conjunction with, at least, one kind of energy storage system. In addition, it is very important to take into account the regulatory barriers and propose solutions to remove them. It was observed that although regulatory aspects can influence the economic feasibility of hybrid projects, little is known about this relationship among regulatory frameworks. The findings presented in this article are important not only for Brazil, but also for other countries that do not have regulations in force to support the use of energy storage systems in hybrid systems.